Nanocrystal V2O5 thin film as hole-extraction layer in normal architecture organic solar cells - Wang, Hao; Li, Ning; Güldal, Nusret Sena; Brabec, Christoph (Organic Electronics, 2012)
Nanocrystal VO dispersion processed thin films are introduced as efficient hole extraction interlayer in normal architecture P3HT:PCBM solar cells. Both thin and rather thick interlayers are studied and demonstrated to work properly in organic photovoltaic. Nanocrystal V OVO layers effectively block electrons and effectively extract holes at the ITO anode. Very constant and high V (above 0.56 V) are easily achieved. Comparable J and PCE are demonstrated for nanocrystal dispersion-processed devices when compared with amorphous sol-gel processed devices. The excellent functionality of nanocrystal VO interlayers in Si-PCPDTBT:PCBM devices further demonstrates the broad application potential of this material class for photovoltaic applications. © 2012 Elsevier B.V. All rights reserved.
Keywords: Electrode buffer layer; Nanocrystals; Organic solar cell; Vanadium oxide